(untitled) (Bangladesh Journal of Medical Science, 2020)
Objective: Oxidative stress has been considered to be one of the main causes for the development of pulmonary hypertension (PH) via leading alteration of pulmonary vasomotor tone induced by hypoxia. The aim of this study is to determine the serum paraoxonase-1 enzyme (PON-1) activity, arylesterase activity, the antioxidant-oxidant status in patients with PH and to compare with healthy controls. Material and Methods: Thirty five healthy ındividuals (mean age 45.7±5.9 years) as a control group and thirty eight patients (mean age 46.5±12.6 years) with a diagnosis of PH wereincluded in thestudy. Serum PON-1 and arylesterase activity, the total antioxidative capacity of plasma (TAC) and total oxidantstatus (TOS) were measured by using colorimetric methods. The Oxidative Stress Index (OSI) wascalculated as TOS/ TACX100. Results: Serum PON1 activity is significantly lower in PH patients when compared with healthy controls (p=0.001). The serum arylesterase activity and TAC, TOS and OSI status were similarin bothgroups. There is inverse correlation between serum PON1 activityand NYHA functionalcapacity (r:-0.649 p=0.001). Furthermore, PON1 activity of study patients are similarin the PH subgroups. Serum activity of PON1 wasfoundto bethe only independent parameter for the presence of PH in binary logistic regression analysis (OR 0.984, 95 % CI 0.977-0.992, p=0.001). Eight patients died follow up period (27.6±14.5 months) and none of theparametersincluding PON1 were associated with mortality. Conclusion: Serum PON1 activity of PH patients is lowerthanhealthypopulation, but does not predictmortality. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.652-658